Mechanochemical activation of a titanium-magnetite mixture: Mössbauer spectroscopy study - Cristobal, Adrian Alberto (2008)
Mechanochemical activation has become a valuable tool in the design and synthesis of novel materials, due to the increased reactivity of activated solids, and the possibility of synthesizing metastable phases not obtainable by conventional methods. In this work, ac magnetic susceptibility, Mössbauer spectroscopy, X-ray diffraction (XRD) and scanning electron microscopy have been employed to study the structural and thermal evolution of a mechanochemically activated Ti-Fe3O4 mixture, with molar ratio Ti:Fe3O4 of 1:2. Upon activation in a high-energy planetary mill, the mixtures undergoes a redox reaction, in which the Ti reduces the Fe ions of the spinel, resulting in a solid solution of variable composition between magnetite (Fe3O4) and ulvospinel (TiFe2O4). The activation results in changes in the magnetic behavior of the mixture, and loss of crystallinity. Mössbauer spectroscopy and XRD show the progressive disappearance of the original phases, and the formation of Fe0, Fe2O3 and ulvospinel. © 2008 Elsevier Ltd. All rights reserved.